French College Students’ Sports Practice and Its Relations with Stress, Coping Strategies and Academic Success - Décamps, Greg; Boujut, Emilie; Brisset, Camille (Frontiers in Psychology, 2012)
College students at university have to face several stress factors. Although sports practice has been considered as having beneficial effects upon stress and general health, few studies have documented its influence on this specific population. The aim of this comparative study was to determine whether the intensity of the college students’ sports practice (categorized into three groups: rare, regular or intensive) would influence their levels of stress and self-efficacy, their coping strategies and their academic success/failure. Three self-completion questionnaires were administered to 1071 French freshmen during their compulsory medical visit at the preventive medicine service of the university. Results indicated that students with intensive sport practice reported lower scores of general stress, academic stress and emotion-focused coping strategies, and higher scores of self-efficacy than those with rare practice. However, the proportion of successful students did not differ significantly between the three groups of sports practice.